KONTEKSTUALISASI KETELADANAN SOSIAL RASULULLAH DI ZAMAN KIWARI - Abu Maskur (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
This paper discusses the concept of the social example of the Prophet Muhammad, which can be used as guidelines and guidance in living a life full of challenges due to the negative impacts of the era of massive industrialization and globalization. One of the negative impacts is that we can see in some religious and political figures whose behavior does not reflect exemplary behavior, such as speaking harshly, insulting and sometimes - not being reluctant - to insult others who are different from him. Ironically, if the religious figure is a Muslim, and the political figure comes from an